SERTIFIKASI PRODUK HALAL UNTUK USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN BANGKALAN - Makhtum, Ahmad; Faraby, Muhammad Ersya (Universitas Muhammadiyah Surabaya, 2021)
Halal certification becomes part of the ecosystem of halal industrial products. Through halal certification will be reflected in halal product guarantee for the community as the mandate of law No 33. 2014 on Halal product guarantee. Therefore, halal product design becomes an important part to estabslishment of halal product ecosystem. Halal certification process will be an important part of the local design for realizing the ecosystem of halal products in order to ensure the existence of halal products. This study uses qualitative method based phenomonology approach in Bangkalan district, which is one of the regencies in Madura Island with the nuance of Islamic in the daily life. The results halal certification on small and micro enterprises is important because it has a direct impact on the economy and community consumption for population. Â In addition from infrastructure of authorities involved in MSMEs is ready and tends to wait for direction in implementation in the fulfillment of halal standards through halal certification. Furthermore that preparations and potentiality halal certification that possessed in outside bureaucracy. Thus, based on this study there will be a description of the condition halal certification in Bangkalan. Therefore that design development of halal product both on a micro and macro scale for halal ecosystem in sustainable level.Keywords: Halal Product Certificated, Small Micro Enterprises; Bangkalan Madura